Pengaruh Pendampingan Kolaboratif Penulisan Artikel Ilmiah terhadap Kompetensi Akademik Mahasiswa PPG - Elfitra, Elfitra; Firdaus, Muliawan; Hutagalung, Trisnawati; Ramadhani, Irham; Frisnoiry, Suci (Jurnal Ilmiah Kanderang Tingang, 2025)
Writing scientific articles is an essential academic competency for students of the Teacher Professional Education (PPG) program. However, many students face difficulties in understanding research methodology, academic structure, as well as data processing and scientific language. To address this issue, Universitas Negeri Medan (UNIMED) initiated a Collaboration for Scientific Article Writing Assistance involving lecturers, mentor teachers, and PPG students. This study employed a qualitative approach using a case study method to evaluate the program’s effectiveness. Data were collected through observations, interviews, and document analysis of article drafts before and after the mentoring sessions. The results show that this mentoring program improved students’ academic competencies, with 85% of participants acknowledging the benefits of the guidance in understanding the structure and quality of scientific writing. Additionally, 70% of students expressed high satisfaction with the program, with the increased number of articles submitted to national and international journals serving as an indicator of its success. However, challenges remain, such as limited time and restricted access to scientific references. Therefore, it is recommended to improve access to academic resources and develop online platforms to support more flexible mentoring. Overall, the results of this study affirm that academic mentoring collaboration is an effective strategy to enhance the scientific writing skills of PPG students and strengthen the academic culture in higher education environments.